2021
DOI: 10.1038/s41598-021-98437-3
|View full text |Cite
|
Sign up to set email alerts
|

The selective NLRP3 inhibitor MCC950 hinders atherosclerosis development by attenuating inflammation and pyroptosis in macrophages

Abstract: NLRP3 inflammasome is a vital player in macrophages pyroptosis, which is a type of proinflammatory cell-death and takes part in the pathogenesis of atherosclerosis. In this study, we used apoE−/− mice and ox-LDL induced THP-1 derived macrophages to explore the mechanisms of MCC950, a selective NLRP3 inhibitor in treating atherosclerosis. For the in vivo study, MCC950 was intraperitoneal injected to 8-week-old apoE−/− mice fed with high-fat diet for 12 weeks. For the in vitro study, THP-1 derived macrophages we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 33 publications
4
53
0
Order By: Relevance
“…Meanwhile miR-30b-5p has been implicated in activation of NLRP3 inflammasome in other studies [ 47 ]. Importantly, many research studies suggest that NLRP3 is involved in pyrophosis of AS [ 12 , 48 ]. Besides, ox-LDL induces the activation of NLRP3 inflammasome in the aorta [ 49 ], which is important for the formation of unstable plaques in AS by promoting Caspase 1 activation of cell pyroptosis involved in ox-LDL-induced apoptosis [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile miR-30b-5p has been implicated in activation of NLRP3 inflammasome in other studies [ 47 ]. Importantly, many research studies suggest that NLRP3 is involved in pyrophosis of AS [ 12 , 48 ]. Besides, ox-LDL induces the activation of NLRP3 inflammasome in the aorta [ 49 ], which is important for the formation of unstable plaques in AS by promoting Caspase 1 activation of cell pyroptosis involved in ox-LDL-induced apoptosis [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, many research studies suggest that NLRP3 is involved in pyrophosis of AS [ 12 , 48 ]. Besides, ox-LDL induces the activation of NLRP3 inflammasome in the aorta [ 49 ], which is important for the formation of unstable plaques in AS by promoting Caspase 1 activation of cell pyroptosis involved in ox-LDL-induced apoptosis [ 48 ]. Furthermore, miR-30b-5p is negatively correlated with NLRP3 [ 21 ], which was confirmed by our results including the dual-luciferase reporter gene system results and qRT-PCR results.…”
Section: Discussionmentioning
confidence: 99%
“…In cardiovascular disease, disseminated periopathogens potentially causes the progression of atheroma lesions [ 83 ]. For example, caspase-11-gasdermin D-mediated pyroptosis and the subsequent pro-inflammatory response in macrophages are involved in the pathogenesis of atherosclerosis [ 117 ], and the selective NLRP3 inhibitor MCC950 hinders atherosclerosis development [ 118 ]. When focusing on rheumatoid arthritis, the disseminated P. gingivalis and A. actinomycetemcomitans may enhance pyroptosis of synovial cells [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that NLRP3 is expressed in a variety of cells and its mediated signaling pathway plays an important role in the progression of diabetes [ 35 , 36 ]. Several studies have shown that activation of NLRP3 can stimulate inflammatory formation and pyroptosis of cells [ 37 , 38 ]. These findings prompted us to detect NLRP3 expression in db/db mice and analyze its association with pancreatic β cells.…”
Section: Discussionmentioning
confidence: 99%